Cleaning Effectiveness of Three NiTi Rotary Instruments: A Focus on Biomaterial Properties - Poggio, Claudio (J Funct Biomater, 2015)
Nickel-titanium (NiTi) instruments are commonly used for shaping the root canal system in endodontic practice. They are more flexible and have better cutting efficiency than conventional stainless steel files. The superelasticity of NiTi rotary files allows the clinicians to produce the desirable tapered root canal form with a reduced tendency to canal transportation and instrument fracture. HyFlex CM instruments are new NiTi rotary instruments with shape memory produced by an innovative methodology (patent pending) that uses a complex heating and cooling treatment that controls the material’s memory. The aim of the present study was to compare the cleaning efficacy of two conventional (Mtwo, Revo-S) Ni-Ti rotary instruments with HyFlex CM. 30 single-rooted freshly extracted teeth were divided into three groups. Root canals were shaped with three NiTi instruments (Mtwo, Revo-S and HyFlex CM) using 5.25% NaOCl and 17% EDTA solutions. Specimens were fractured longitudinally and prepared for SEM analysis at standard magnification of 1000×. The presence/absence of debris smear layer and the presence/absence of smear layer at coronal, middle, and apical third of each canal were evaluated using a 5-step scale for scores. Numeric data were analyzed using Kruskall-Wallis and Mann-Whitney U statistical tests and significance was predetermined at P < 0.05. This study revealed significant differences among the various groups. Despite some minor differences, all instruments removed smear layer and debris produced during instrumentation. HyFlex CM seem to be not so effective in promoting cleanliness of root canal walls and in removing smear layer from dentine if compared to Mtwo and Revo-S.